Education for Peace: social representations of young people in public High School about tolerance/intolerance (Research, Society and Development, 2022)
The objective was to analyze the social representations (SR) of young people from Public High Schools regarding Tolerance/Intolerance, based on the articulation of the Theory of Social Representations in the field of Education for Peace. The research was developed during the years 2017 to 2021 in a public high school in the city of São Paulo (SP) in two stages. In the first stage, aiming to establish an exploratory mapping related to information, attaoitudes, and the structure of the representational field, we applied a questionnaire guided by the Free Word Association Technique, with 112 young people. In order to facilitate the data analysis, they were processed using the IRaMuTeQ software. In the second stage, deepening the investigation through the analysis of the attitudinal dimension, projective scenarios on Tolerance/Intolerance were developed and validated, which were later applied to 6 young people in a focus group. To assist in data analysis, content analysis was used. We conclude that the SR of Tolerance/Intolerance for the grouping, possibly, are objectified: in the historical heritage; in the circumstantial relationship between EGO–ALTER–OBJECT and CONTEXT; in personification; in the social actions of “to bear”/“not to bear”, “to take it”/“not to take it”; in transversal elements – freedom of thought and speech, fundamental rights; social minorities. Moreover, the possible anchors would be: in the dyad of presence/absence of dialogue; in the belief in the enlightenment/ignorance dyad; in moral elements; in the legitimacy of institutions as conflict mediation agencies; rooted in elements pertaining to the sensitive sphere.